Optimalisasi Keterampilan Ziarah Kubur Berkelompok pada Mahasiswa di Provinsi Riau - Edison; Lukman; Salman, Nola Fibriyanti Bte (At-Tadris: Journal of Islamic Education, 2025)
This study aims to investigate the skills of grave pilgrimage with correct procedures for PTKI and PTU students in Riau. This study also compares the performance of grave pilgrimage between PTKI students and PTU students. To find these objectives, this study used a qualitative experimental method. The data collected in this study is the predicate of grave pilgrimage skills performed by students. The data were then analyzed using the framework analysis method which includes the stages of socialization of grave pilgrimage procedures; observation of implementation by students as research subjects, data interpretation and comparison of grave pilgrimage performance between PTKI students and PTU students. The results showed that 50% of the research subjects achieved the predicate of skillful and the other 50% achieved the predicate of very skillful in the performance of grave pilgrimage. The Independent Sample t-Test comparison test of students' grave pilgrimage performance score data shows that there is indeed a significant difference in grave pilgrimage performance between students from PTKI and students from PTU. Future research should examine the effect of the implementation of grave pilgrimage on the tendency of students to remember the afterlife, remember death, the attitude of zuhud students against the glitter of the world and its impact in preventing students from speaking foul words